Exílio, literatura, intelectuais e política em Mariel: Revista de Literatura y Arte (1983-1985) - Caroline Maria Ferreira Drummond (2018)
Mariel Revista de Literatura y Arte was founded in 1983 in Miami by Cuban writers exiled in the United States after the massive exile of Mariel (1980), and circulated until 1985 in the United States, Latin America and Europe. Its Board of Directors was composed by the writers Reinaldo Arenas, Reinaldo García Ramos, and by the plastic artist and writer Juan Abreu. As a literary magazine, one of its main objectives was to divulge Cuban literature and art, especially the one produced by writers of the selfproclaimed Mariel generation, placing itself as an identity link between these artists. The publication also brought together dissidents who left the island in the 1960s and 1970s, such as the renowned Cuban anthropologist Lydia Cabrera and participants in the El Puente editorial project. The collective editorial project was opposed to the Cuban revolutionary regime, and declared itself anti-communist, anti-totalitarian, defender of democracy and individual liberties, possessing strong character of denunciation. In our study, we aimed to analyze how the intellectuals that colaborated in the magazine debated the exile, the function of the intelectual and literature, the Cuban revolutionary regime and the national identity. Our central proposal is to understand the trajectory of the collective editorial project and how it constituted a political opposition to the Cuban revolutionary government during exile in the United States. In this way, we reconstituted the funding forms of the magazine, the sociability networks established and how its collaborators dialogued with the programmatic editorialism of the project.